Achilles tendoscopy for non insertional Achilles tendinopathy. A case series study. Issue 4 (June 2020) - Wagner, Pablo; Wagner, Emilio; Ortiz, Cristian; Zanolli, Diego; Keller, Andres; Maffulli, Nicola
Highlights: Different operative procedures exist for Achilles tendinopathy treatment with no clear advantage of one over another. Wound healing complications is the main complication of open procedures. Tendoscopy for non-insertional Achilles tendinopathy is a procedure with good clinical outcomes and minimal morbidity. Tendoscopy offers a minimally invasive approach which does not compromise future procedures. Abstract: Background: Achilles non-insertional tendinopathy is usually treated with conservative means. If resistant to a rehabilitation protocol surgical treatment could be proposed. The aim of this research is to report the mid-term clinical results of endoscopic assisted surgery for patients suffering from recalcitrant painful non-insertional Achilles tendinopathy. Methods: A consecutive series of 11 patients (6 men and 5 women), median age of 54 (range 40–67) years, with chronic recalcitrant painful non-insertional Achilles tendinopathy were included. All patients completed at least 20 physical therapy sessions and 6 months of no sports activities before surgery. All underwent Achilles tendoscopy, without tendon excision or transfer with a median follow-up of 87 (27–105) months. We report the preoperative symptoms duration, treatment before surgery, complications and satisfaction after surgery, return to previous sport level, and postoperative VISA-A score. Results: Mean preoperative symptoms duration was 1 year, having all performed at least 20 physical therapy sessions. No postoperative complications were reported, achieving a complete satisfaction in 10 of 11 patients. All patients returned to their preoperative sports level with a median postoperative VISA-A functional score of 100 (30–100) points. Conclusions: The mid-term results of Achilles tendoscopy in patients with chronic painful non-insertional Achilles tendinopathy are satisfactory with a rapid rehabilitation. This procedure is safe and has a low complication rate. Level of Evidence: IV. Retrospective case series.